2017
DOI: 10.1101/106971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FAM83G/PAWS1 controls cytoskeletal dynamics and cell migration through association with the SH3 adaptor CD2AP

Abstract: Summary statement:PAWS1/FAM83G controls cell migration by influencing the organisation of F-actin and focal adhesions and the distribution of the actin stress fibre network through its association with CD2AP.. CC-BY-NC-ND 4.0 International license not peer-reviewed) is the author/funder. It is made available under aThe copyright holder for this preprint (which was . http://dx.doi.org/10.1101/106971 doi: bioRxiv preprint first posted online Feb. 8, 2017; . CC-BY-NC-ND 4.0 International license not peer-review… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…1A; fig S1), we postulated that this domain might mediate the observed interaction between FAM83 and CK1 proteins. To map the minimal domain within FAM83 proteins that can interact with CK1 isoforms, we co-expressed Myc-tagged FAM83G fragments with full-length hemagglutinin (HA)-tagged CK1α in FAM83G -/- U2OS cells (28) and performed coimmunoprecipitation experiments (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A; fig S1), we postulated that this domain might mediate the observed interaction between FAM83 and CK1 proteins. To map the minimal domain within FAM83 proteins that can interact with CK1 isoforms, we co-expressed Myc-tagged FAM83G fragments with full-length hemagglutinin (HA)-tagged CK1α in FAM83G -/- U2OS cells (28) and performed coimmunoprecipitation experiments (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The following constructs were generated: pcDNA5-FRT/TO GFP-FAM83A (DU44235), pcDNA5-FRT/TO GFP-FAM83B (DU44236), pcDNA5-FRT/TO GFP-FAM83C (DU42473), pcDNA5-FRT/TO GFP-FAM83D (DU42446), pcDNA5-FRT/TO GFP-FAM83E (DU44237), pcDNA5-FRT/TO GFP-FAM83F (DU44238), pcDNA5-FRT/TO GFP-FAM83G (DU33272), pcDNA5-FRT/TO GFP-FAM83H (DU44239), pcDNA5-FRT/TO GFP-FAM83C (D259A) (DU28479), pcDNA5-FRT/TO GFP-FAM83C (F293A) (DU28480), pcDNA5-FRT/TO GFP-FAM83E (D243A) (DU28481), pcDNA5-FRT/TO GFP-FAM83E (F277A) (DU28482), pcDNA5-FRT/TO GFP-FAM83F (D250A) (DU28268), pcDNA5-FRT/TO GFP-FAM83F (F284A) (DU28488), pcDNA5-FRT/TO GFP-FAM83G (D262A) (DU28476), pcDNA5-FRT/TO GFP-FAM83G (F296A) (DU28477), pcDNA5-FRT/TO GFP-FAM83H (D236A) (DU28428), pcDNA5-FRT/TO GFP-FAM83H (F270A) (DU28487), pcDNA5-FRT/TO mCherry-CK1α (DU28407), pcDNA5-FRT/TO mCherry-CK1α (N141A) (DU28839), pcDNA5-FRT/TO GFP-FAM83H(M1-L284)-FAM83G(S311-P823) (DU28683), pcDNA5-FRT/TO GFP-FAM83G(M1-V310)-FAM83H(V285-K1179) (DU28688), pcDNA5-FRT/TO FAM83A-GFP (DU42864), pcDNA5-FRT/TO FAM83B-GFP (DU42833), pcDNA5-FRT/TO FAM83C-GFP (DU42825), pcDNA5-FRT/TO FAM83D-GFP (DU42835), pcDNA5-FRT/TO FAM83E-GFP (DU42826), pcDNA5-FRT/TO FAM83F-GFP (DU42832), pcDNA5-FRT/TO FAM83G-GFP (DU42816), pcDNA5-FRT/TO FAM83H-GFP (DU42865), pcDNA5-FRT/TO GFP only (DU41455), pcDNA5-FRT/TO GFP-FAM83H (F274A) (DU28658), pcDNA5-FRT/TO GFP-FAM83H (F270, 274A) (DU28182), pcDNA5-FRT/TO FLAG-FAM83G (DU33274), pcDNA5-FRT/TO FLAG-FAM83G (F296A) (DU28024), pcDNA5-FRT/TO FLAG-FAM83G (F296A, F300A) (DU28026), pcDNA5-FRT/TO FLAG-FAM83G (F300A) (DU28025), pCS2+ HA-CK1α (DU28216), pCMV5-FLAG TTBK2 (DU19028), pCMV-FLAG-CK1γ (DU5580), pCS2+ HA CK1δ (DU28189), pcDNA5-FRT/TO mcherry-CK1ε (DU28406). Myc-xFAM83G (Xenopus laevis FAM83G) constructs have been described previously (28). For CRISPR/Cas9 gene editing, pBABED P U6 FAM83H KO sense gRNA (DU52010), pX335-CAS9-D10A FAM83H KO antisense gRNA (DU52026), pBABED P U6 FAM83G KI sense gRNA (DU48528), pX335-Cas9-D10A FAM83G KI antisense gRNA (DU48529), pEX-K4 FAM83G Cter GFP donor (DU48585), pBABED P U6 FAM83B KI sense gRNA (DU54494), pX335-Cas9-D10A FAM83B KI antisense gRNA (DU54504), and pEX-K4 FAM83B Nter GFP donor (DU54547) were generated.…”
Section: Methodsmentioning
confidence: 99%
“…PAWS1 deficiency causes severe defects in F-actin organisation and distribution, as well as lamellipodial organisation, resulting in impaired cell migration. The dynamic association of PAWS1 with the actin/cytoskeletal regulator CD2AP at lamellae appears to be essential for PAWS1 to control actin organisation and cellular migration [ 36 ]. Interestingly, deficiency of CD2AP phenocopies the actin and cell migration defects observed when cells are depleted of PAWS1 [ 36 ].…”
Section: The Role Of Fam83g In Cell Signalling Morphology and Diseasmentioning
confidence: 99%
“…The dynamic association of PAWS1 with the actin/cytoskeletal regulator CD2AP at lamellae appears to be essential for PAWS1 to control actin organisation and cellular migration [ 36 ]. Interestingly, deficiency of CD2AP phenocopies the actin and cell migration defects observed when cells are depleted of PAWS1 [ 36 ]. Recently, we showed that PAWS1 overexpression in Xenopus embryos activates Wnt signalling and causes complete axis duplication.…”
Section: The Role Of Fam83g In Cell Signalling Morphology and Diseasmentioning
confidence: 99%
“…CD2-associated protein (CD2AP) is a cortactin-binding scaffold protein that controls actin dynamics and participates in membrane trafficking during endocytosis by interacting with dynamin, synaptojanin1, endophilin, and nephrin ( 49 , 95 ). CD2AP has three Src homology 3 (SH3) domains and a coiled-coil domain contributing to its functions on actin dynamics and endocytosis by interactions with other proteins containing proline-rich domains ( 96 ). Interestingly, mice lacking Cd2ap develop nephrotic syndrome and die at 6–7 weeks of age due to kidney failure ( 21 ).…”
Section: Endocytosis In Podocyte Homeostasis and Diseasementioning
confidence: 99%